Dextromethorphan - A widely-used cough suppressant - Induces local anaphylaxis via MRGPRX2 on mast cells. (1st October 2020) - Hu, Tian; Hou, Yajing; Lu, Jiayu; Wang, Xiangjun; Wei, Di; Wang, Cheng
Abstract: Dextromethorphan (DM) is a cough suppressant available in many prescribed and over-the-counter medications. Adverse reactions induced by DM have been regularly reported, including allergic skin reactions in some cases. However, the underlying mechanisms of local anaphylaxis induced by DM have not been elucidated. In this study, we found that DM could activate mast cells to increase calcium mobilization and release β-hexosaminidase, histamine, tumor necrosis factor-α, MCP-1, and IL-8 in a dose-dependent manner. The allergic reactions were confirmed by hind paw swelling and extravasation assay in vivo . Furthermore, DM was revealed to induce local anaphylaxis via MRGPRX2 by the mast cell-deficient kit W-sh/W−sh mice and MRGPRX2 knockdown mast cells. And the MRGPRX2-HEK293/CMC analysis and frontal analysis also showed that DM has a considerable affinity with MRGPRX2. Together, our findings suggest that close monitoring should be drawn on patients with DM for its potential anaphylaxis via MRGPRX2. Highlights: Dextromethorphan (DM) was firstly found to induce anaphylaxis in vitro and in vivo. MRGPRX2 was confirmed to be critical to anaphylaxis induced by DM. Close monitoring should be drawn on patients with drugs containing DM.